Pengaruh Pembelajaran Akidah Akhlak terhadap Perilaku Siswa di MTs Labibia Kota Kendari - Aprilia, Dina; Abbas, Abbas; Herman, Herman; Halistin, Halistin (IAIN KENDARI, 2023)
The background of this research is the teaching of aqidah morals which is not yet appropriate in the formation of student behavior at MTs Labibia, Kendari City. This research aims to find out: 1) Aqidah Akhlak learning at MTs Labibia, Kendari City. 2) Knowing the behavior of students at MTs Labibia, Kendari City. 3) Knowing the effect of learning aqidah morals on student behavior at MTs Labibia, Kendari City. This research is a quantitative research using survey method. The sampling technique in this study was saturated sampling, the number of samples used was 83 students. Data collection techniques in this study used questionnaires and observation. The data analysis technique used is descriptive and inferential analysis. From the results of the study showed 1) learning aqidah morals at MTs Labibia has an average of 73 with a minus category percentage of 34%. 2) student behavior at MTs Labibia has an average of 127 with an enough category of 42%. 3) there is an effect of learning aqidah morals on student behavior at MTs Labibia with a significant value of 0.00 <0.05 with a contribution of 11.1%, so it can be concluded that variable X affects variable Y.